2015
DOI: 10.1007/s10447-015-9249-0
|View full text |Cite
|
Sign up to set email alerts
|

The Counseling Profession in Kuwait: Its Journey and Future

Abstract: A review of mental health counseling and therapy in Kuwait revealed that it is still in a developmental stage. While statistical data are lacking, there remains anecdotal evidence of growth since the mid-twentieth century, albeit with a setback as a consequence of the Iraqi invasion and its aftermath in the 1990s. Re-invigorated more recent growth indicates the need for and an interest in the field, even though psychiatric disorders are still highly stigmatized within Kuwait. The purpose of this paper is to ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A third piece of the explanation relates to generational differences in education. Kuwait University is the most established university in Kuwait, and its College of Social Sciences was established only in 1998 (Al-Qimlass, 2015). Circa 1995, an estimated 21% of the Kuwaiti population was illiterate (Bahgat, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A third piece of the explanation relates to generational differences in education. Kuwait University is the most established university in Kuwait, and its College of Social Sciences was established only in 1998 (Al-Qimlass, 2015). Circa 1995, an estimated 21% of the Kuwaiti population was illiterate (Bahgat, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, mental healthcare services in Qatar have been the remit of psychiatrists within secondary care, where a new strategy is supporting transition towards community-based care [18]. In Kuwait, a review of mental health counselling and therapy revealed that it was still in a developmental stage [19].…”
Section: Introductionmentioning
confidence: 99%